Antagonism at the NR2B subunit of NMDA receptors induces increased connectivity of the prefrontal and subcortical regions regulating reward behavior - Gass, Natalia; Inta, Dragos; Meyer-Lindenberg, Andreas; Gass, Peter; Sartorius, Alexander (Psychopharmacology, 2018)
RationaleEvidence indicates that ketamine’s rapid antidepressant efficacy likely results from its antagonism of NR2B-subunit-containing NMDA receptors (NMDAR). Since ketamine equally blocks NR2A- and NR2B-containing NMDAR, and has affinity to other receptors, NR2B-selective drugs might have improved therapeutic efficiency and side effect profile.ObjectivesWe aimed to compare the effects of (S)-ketamine and two different types of NR2B-selective antagonists on functional brain networks in rats, in order to find common circuits, where their effects intersect, and that might explain their antidepressant action.MethodsThe experimental design comprised four parallel groups of rats (N = 37), each receiving (S)-Ketamine, CP-101,606, Ro 25-6981 or saline. After compound injection, we acquired resting-state functional magnetic resonance imaging time series. We used graph theoretical approach to calculate brain network properties.ResultsKetamine and CP-101,606 diminished the global clustering coefficient and small-worldness index. At the nodal level, all compounds induced increased connectivity of the regions mediating reward and cognitive aspects of emotional processing, such as ventromedial prefrontal cortex, septal nuclei, and nucleus accumbens. The dorsal hippocampus and regions involved in sensory processing and aversion, such as superior and inferior colliculi, exhibited an opposite effect.ConclusionsThe effects common to ketamine and NR2B-selective compounds were localized to the same brain regions as those reported in depression, but in the opposite direction. The upregulation of the reward circuitry might partially underlie the antidepressant and anti-anhedonic effects of the antagonists and could potentially serve as a translational imaging phenotype for testing putative antidepressants, especially those targeting the NR2B receptor subtype.
Gesehen am 09.12.2019